2009
DOI: 10.1111/j.1365-2966.2009.14722.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the composite stellar population in M32

Abstract: We obtained long‐slit spectra of high signal‐to‐noise ratio of the galaxy M32 with the Gemini Multi‐Object Spectrograph at the Gemini‐North telescope. We analysed the integrated spectra by means of full spectral fitting in order to extract the mixture of stellar populations that best represents its composite nature. Three different galactic radii were analysed, from the nuclear region out to 2 arcmin from the centre. This allows us to compare, for the first time, the results of integrated light spectroscopy wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 62 publications
12
41
2
Order By: Relevance
“…Even though we do not constrain well the extent of the "confusion zone" in the high Z regime, the young component is stronger than the fake bursts we found: it accounts for 20% of the light (in a similar wavelength range) while we found maximum spurious contributions of 10%-12%. Hence, our result supports the claims of Coelho et al (2009), mainly that there has been a recent burst of star formation in the center of M32, while the young component seen in the outskirts is also compatible with being an artifact due to the blue HB morphology of the system.…”
Section: M32supporting
confidence: 81%
See 2 more Smart Citations
“…Even though we do not constrain well the extent of the "confusion zone" in the high Z regime, the young component is stronger than the fake bursts we found: it accounts for 20% of the light (in a similar wavelength range) while we found maximum spurious contributions of 10%-12%. Hence, our result supports the claims of Coelho et al (2009), mainly that there has been a recent burst of star formation in the center of M32, while the young component seen in the outskirts is also compatible with being an artifact due to the blue HB morphology of the system.…”
Section: M32supporting
confidence: 81%
“…The rightmost panel of Figure 6 of Coelho et al 2009 shows that except for the nucleus, a large fraction (about ≈50 %) of the light of M32 is produced by a [Fe/H] < −1.2 old stellar population. Our study shows that in this regime, a spurious young burst accounting for ≈5% is indeed likely to appear.…”
Section: M32mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while Fan & de Grijs (2012) Photometric, spectral indices or spectral fitting methods differ not only in their technical details, but also their underlying stellar population models differ in their choice of evolutionary tracks, the libraries of stellar spectra and in their implementation details, such as interpolations. Coelho et al (2009), for example, made an analysis of the stellar population in M 32 and has shown that using the same method with different SSP models result in different age and metallicity distributions; they conclude that choosing different SSP models from the literature might yield different results of age and metallicity at the quantitative level, even though a qualitative agreement is met. Dias et al (2010) also found evidence of this dependence of the results on the choice of SSP models when studying integrated spectra of GCs in the Small Magellanic Cloud.…”
Section: Stellar Populations In M 31 Gcsmentioning
confidence: 99%
“…M32 appears to have had one or more relatively recent episodes of star formation (within the last 3 Gyr: e.g., O'Connell 1980;Rose 1985;Trager et al 2000;Coelho et al 2009). O'Connell (1980) concluded that models fail to reproduce M32 with a single old-age and solar-metallicity population.…”
Section: Introductionmentioning
confidence: 99%